The association of engagement in substance use treatment with negative separation from the military among soldiers with post-deployment alcohol use disorder. (1st April 2021) - Gray, Joshua C.; Larson, Mary Jo; Moresco, Natalie; Ritter, Grant A.; Dufour, Steven; Milliken, Charles S.; Adams, Rachel Sayko
Highlights: Among soldiers with post-deployment AUD, 40 % initiated and 24 % engaged in treatment. 35 % of soldiers with AUD had a negative separation from the military. Engagement in SUD treatment was associated with increased negative separation. To improve retention, SUD treatment should be offered earlier to soldiers with AUD. Abstract: Background: Alcohol use disorder (AUD) reduces the health of soldiers and the readiness of the Armed Forces. It remains unknown if engagement in substance use treatment in the Military Health System improves retention in the military. Methods: The sample consisted of active duty soldiers returning from an Afghanistan/Iraq deployment in fiscal years 2008–2010 who received an AUD diagnosis within 150 days of completing a post-deployment health re-assessment survey (n = 4, 726). A Heckman probit procedure was used to examine predictors of substance use treatment initiation and engagement in accordance with Healthcare Effectiveness Data and Information Set (HEDIS) criteria. Cox proportional hazard modeling was used to examine the association between treatment engagement and retention, defined as a negative separation for a non-routine cause (e.g., separation due to misconduct, poor performance, disability) from the military in the two years following the index AUD diagnosis. Results: 40 % of soldiers meeting HEDIS AUD criteria initiated and 24 % engaged in substance use treatment. Among soldiers diagnosed with AUD, meeting criteria for treatment engagement was associated with a significantly higher hazard of having a negative separation compared to soldiers who did not engage in treatment. Conclusions: Rates of initiation and engagement in substance use treatment for post-deployment AUD were relatively low. Soldiers with AUD who engaged in substance use treatment were more likely to have a negative separation from the military than soldiers with AUD who did not engage. Our findings imply that in the study cohort, treatment did not mitigate negative career consequences of AUD.